Penerapan Model Blended Learning terhadap Peningkatan Hasil Belajar Matematika Materi Volume Bangun Ruang Kelas V di Masa Pandemi - Ihda Amatiddiniyyah (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2022)
Abstract Blended learning is widely applied in several schools during this pandemic. Blended learning is a learning using two directions, namely face to face and online. In learning mathematics, especially the material for volumetric figures, the results are often unsatisfactory. This is due to learning that is less effective and tends to be monotonous. This study aims to determine the level of understanding of the volume of Solid Figure in students who use face-to-face learning and students who use blended learning models. The method used in this study is a quantitative method of Independent Sample T Test with a quasi-experimental design. The data collection process used pre-test and post-test with multiple choice questions. The population is all fifth grade students of SD Negeri Mekarsari II as the experimental class and all students of SD Negeri Nagacipta 01 as the control class. The sample used is 24 students. The result is that the implementation of the blended learning method can significantly improve the mathematics learning outcomes of solid figure volumes. Keywords: Implementation Blended Learning, Improved Learning Outcomes, Solid Figure Volume Abstrak Pembelajaran blended learning banyak diterapkan di beberapa sekolah dalam masa pandemi ini. Blended learning adalah suatu pembelajaran dengan menggunakan dua arah yaitu tatap muka dan online. Dalam pembelajaran matematika khususnya materi volume bangun ruang seringkali hasilnya tidak memuaskan. Hal ini disebabkan pembelajaran yang kurang efektif dan cenderung monoton. Penelitian ini bertujuan untuk mengetahui tingkat pemahaman materi volume bangun ruang pada siswa yang menggunakan pembelajaran tatap muka dan siswa yang menggunakan model blended learning. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif Independent Sample T Test dengan desain eksperimen semu (quasy experimental design). Proses pengumpulan data menggunakan pre-test dan post-test dengan soal pilihan ganda. Populasinya seluruh siswa kelas V SD Negeri Mekarsari II sebagai kelas eksperimen dan seluruh siswa SD Negeri Nagacipta 01 sebagai kelas kontrol. Sampel yang digunakan adalah 24 siswa. Hasilnya adalah penerapan metode blended learning secara signifikan dapat meningkatkan hasil belajar matematika materi volume bangun ruang. Kata kunci : Penerapan Blended Learning, Peningkatan Hasil Belajar, Volume Bangun Ruang.